Synthetic sorbent materials based on metal sulphides and oxides. (2020) - Sofronov, D. S; Belikov, K.N; Rucki, M; Lavrynenko, S.N; Siemiątkowski, Z; Bryleva, E. Yu; Odnovolova, O.M
No abstract available